Transcriptome and N6-Methyladenosine RNA Methylome Analyses in Aortic Dissection and Normal Human Aorta - Zhou, Xianwu; Chen, Zerui; Zhou, Jianrong; Liu, Yaorong; Fan, Ruixin; Sun, Tucheng (Frontiers in Cardiovascular Medicine, 2021)
OBJECTIVE To investigate the N6-methyladenosine (m6A) modification and the expressions of the m6A regulatory genes in the acute aortic dissection (AD). METHODS MeRIP-seq and RNA-seq experiments of aortic media tissue samples obtained from AD (n=4) and Controls (n=4) were conducted. m6A methylation quantification was used to measure the total mRNA m6A level. The five m6A regulators mRNA expressions were analyzed by quantitative polymerase chain reaction (qPCR). Western blot analyses and immunofluorescence staining were used to detect the difference of METTL14 protein expression in the aortas of AD and Normal. RESULTS Among AD patients, we detected significantly elevated levels of m6A in total RNA. Compared with the normal group, the up methylated coding genes of AD were primarily enriched in the processes associated with extracellular fibril organization, while the genes with down methylation were enriched in the processes associated with cell death regulation. Furthermore, many differentially methylated m6A sites (DMMSs) coding proteins were mainly annotated during the extracellular matrix and inflammatory responses. CONCLUSIONS These findings indicate that differential m6A methylation and m6A regulatory genes, including MTEEL14 and FTO, may act on functional genes through RNA modification, thereby regulating the pathogenesis of aortic dissection.